2019
DOI: 10.1111/dmcn.14367
|View full text |Cite
|
Sign up to set email alerts
|

CHD2‐related epilepsy: novel mutations and new phenotypes

Abstract: The aim of this report was to refine the genotypes and phenotypes of chromodomain helicase DNA‐binding protein 2 (CHD2)‐related epilepsy. Seventeen patients with CHD2 mutations were enrolled. CHD2 mutations were identified by application of next‐generation sequencing of epilepsy or whole exome sequencing. Sixteen mutations were identified, among which 15 have not yet been reported. Thirteen mutations were de novo. Age at seizure onset ranged from 3 months to 10 years 5 months. Seizures observed were generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…The distressing thing is that compared with her daughter's refractory epilepsy, her seizures have always been well controlled (Petersen et al, 2018). In 2020, Chen et al reported a sporadic case inherited from an unaffected father with c.5153+2T>C variant of CHD2 gene and dizygotic twins inherited from the affected father with c.5232G>A (p. Met1744Ile) (Chen et al, 2020). To our surprise, the five mutations in patients did not occur again in other cases.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The distressing thing is that compared with her daughter's refractory epilepsy, her seizures have always been well controlled (Petersen et al, 2018). In 2020, Chen et al reported a sporadic case inherited from an unaffected father with c.5153+2T>C variant of CHD2 gene and dizygotic twins inherited from the affected father with c.5232G>A (p. Met1744Ile) (Chen et al, 2020). To our surprise, the five mutations in patients did not occur again in other cases.…”
Section: Discussionmentioning
confidence: 85%
“…It is mapped to chromosome 15q26.1 and is considered an ATP-dependent chromatin remodeling that regulates the transcription expression of many genes (Lamar and Carvill, 2018;Carvill and Mefford, 2015). Some studies have demonstrated that pathogenic variants of the CHD2 gene are associated with childhood-onset developmental and epileptic encephalopathy (DEE), which is a severe form of neurodevelopmental disorder with a wide range of phenotypic variability, including autism spectrum disorder (ASD), intellectual disability (ID), developmental delay, microcephalus, behavioral anomalies, facial dysmorphisms, and several types of epilepsy (Carvill and Mefford, 2015;Thomas et al , 2015;Verhoeven et al, 2016;Chen et al, 2020). Recently, Chen et al presented the largest single case series of patients with CHD2-related epilepsy and then comprehensively reviewed 53 published cases in the literature through seizure onset age, seizure types, developmental outcome, electroencephalogram (EEG), brain magnetic resonance imaging (MRI), and diagnoses, among others, which improved the understanding on the relationship between genotype and phenotype (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic variants in CHD1 lead to a developmental disorder associated with developmental delay, speech apraxia, autism, hypotonia, and facial dysmorphic features (Pilarowski et al 2018 ). CHD2 pathogenic variants cause a developmental and epileptic encephalopathy (Suls et al 2013 ; Chen et al 2020 ). Disease-causing variants in CHD7 and CHD8 cause CHARGE syndrome and a syndromic form of autism spectrum disorder, respectively (Vissers et al 2004 ; Zentner et al 2010 ; O’Roak et al 2011 ; Merner et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…All CHD genes are evolutionary constrained in human populations, with significantly fewer truncating and missense variants than expected by chance (Karczewski et al 2020 ), but only six of the nine CHD members have been associated with human disorders so far (Zentner et al 2010 ; Merner et al 2016 ; Weiss et al 2016 , 2020 ; Pilarowski et al 2018 ; Blok et al 2018 ; Chen et al 2020 ). Together with CHD6 and CHD9, CHD5 has not yet been associated with a human disease.…”
Section: Introductionmentioning
confidence: 99%